Multi-Faceted Surface Effect on Heat Transfer Performance and Flow Dynamics at the Onset of Optimum Nusselt Number - Amir F.M.; Yusoff M.Z.; Hassan S.H.A. (Praise Worthy Prize, 2023)
A multi-faceted cylinder of half-circle, flat, and triangle surfaces is investigated numerically in this study. The flow characteristics were observed. Their effects on thermal performance were investigated under various cross-flow conditions and blocking ratios. The multi-faceted cylinder's effectiveness compared to the circular cylinder in terms of a heat exchanger is also presented. The multi-faceted cylinder suffers an average of 0.47% drop in effectiveness relative to the circular cylinder. However, despite producing a higher heat transfer coefficient, the circular cylinder has a lower Nusselt number contributed by a higher Strouhal number. A lower Strouhal number in a multi-faceted cylinder enables it to have a higher Nusselt number in the downstream surface than the circular cylinder. This is due to better fluid contact through flow attachment at the flat surface and the sharp edge. The multi-faceted cylinder's asymmetrical surface also creates higher velocity imbalances in the upper and lower half of the channel, which produced a distinct drag coefficient pattern. The multi-faceted cylinder offers enhanced convective heat transfer compared to the circular cylinder but with relatively higher drag under increasing Reynolds number. 2021 Praise Worthy Prize S.r.l. - All rights reserved.